CONCENTRATIONS OF HEAVY METALS IN THREE TILAPINE SPECIES OF AN ABANDONED GOLD MINE RESERVOIR IN IGUN, NIGERIA - LAWAL, O.A; KOMOLAFE, O.O. (Nigerian Journal of Fisheries, 2012)
The concentrations of Arsenic, Chromium, Lead and Zinc in the fillet and gills of three economically important tilapine species: Tilapia zillii, Hemichromis fasciatus and Sarotherodon galilaeus from an abandoned gold mining reservoir in Igun village, Osun state, Nigeria were investigated between May 2008 and May 2009. Varying high concentrations of Arsenic, Chromium and Zinc were recorded in all fish organs collected from the reservoir in wet and dry seasons. Irrespective of the time of collection, Chromium was the most bioaccumulated heavy metal in the gills and fillet of all fish species. Analysis, showed that H. fasciatus bioacccumulated Arsenic, Zinc and Chromium at higher concentrations when compared to other fishes. It was noted that the concentration of Arsenic, Chromium and Zinc in T. zillii, H. fasciatus and S. galilaeus were generally high when compared to the World Health Organisation and Federal Environmental Protection Agency maximum allowable standards in fish food. Lead concentrations in all fish samples were non-detectable.